Educational Technology Adoption in India : Theory of Consumption Values Perspective - Aaradhi, Vaibhav; Chakraborty, Debarun (Prabandhan: Indian Journal of Management, 2024)
Purpose : The Indian education sector has undergone significant reforms, accelerated by the nationwide lockdown after the pandemic, and this increased demand for EdTech platforms. Internet-based learning systems gained quick acceptance among students. India has experienced significant growth in digital teaching-learning systems and EdTech platforms in the past few years; this study explored the technology adoption behavior of Indian application users, focusing on the theory of consumption values and determining the factors that drive this behavior. Design/Methodology/Approach : This study used an explorative mixed-method research approach to conduct focus group discussions with 100 users for questionnaire development and conducting a cross-sectional survey, which was conducted in both online and offline modes to EdTech application users; 513 complete responses so received were analyzed using structural equation modeling. Findings : The functional, social, conditional, and epistemic values significantly impacted technology-adopted behavior in the Indian scenario for EdTech applications. Research Implications : The results of this study provided policymakers and EdTech platform developers with valuable insights into the elements influencing technology adoption. Originality/Value : Considering the Indian government’s thrust toward online education and blended learning approach post-COVID-19, the EdTech sector anticipated exponential growth. Thus, the factors driving technology adoption required research.